A Framework of Non-Halal Certification Practices: Law Perspective - Haryanti, Tuti; Saleng, Abrar; Miru, Ahmadi; Sitorus, Winner (International Journal of Psychosocial Rehabilitation, 2020)
submission of halal certification is voluntary in nature and becomes mandatory. Business actors who have obtained halal certificates must follow the halal production requirements. In fact, some business actors are unable to maintain the halal nature of the product. This study aims to uncover consumers' losses and formulate forms of legal liability of business actors for consumer losses. This type of research used is normative legal research with primary and secondary legal materials then analyzed qualitatively. The results showed that business actors who were unable to maintain the halal of the product both in terms of the use of food ingredients or the production process caused losses to consumers, namely spiritual losses, property losses, health losses, social and mental losses. Consumer losses as a basis for business actors' responsibility to consumers by providing cumulative compensation both material and immaterial losses.